Controlling Metallophilic Interactions in Chiral Gold(I) Double Salts towards Excitation Wavelength‐Tunable Circularly Polarized Luminescence. (5th March 2020) - Yang, Jian‐Gong; Li, Kai; Wang, Jian; Sun, Shanshan; Chi, Weijie; Wang, Chao; Chang, Xiaoyong; Zou, Chao; To, Wai‐Pong; Li, Ming‐De; Liu, Xiaogang; Lu, Wei; et al.
Abstract: Materials exhibiting excitation wavelength‐dependent photoluminescence (Ex‐De PL) in the visible region have potential applications in bioimaging, optoelectronics and anti‐counterfeiting. Two multifunctional, chiral [Au(NHC)2 ][Au(CN)2 ] (NHC=(4R, 5R)/(4S, 5S)‐1, 3‐dimethyl‐4, 5‐diphenyl‐4, 5‐dihydro‐imidazolin‐2‐ylidene) complex double salts display Ex‐De circularly polarized luminescence (CPL) in doped polymer films and in ground powder. Emission maxima can be dynamically tuned from 440 to 530 nm by changing the excitation wavelength. The continuously tunable photoluminescence is proposed to originate from multiple emissive excited states as a result of the existence of varied Au I ⋅⋅⋅Au I distances in ground state. The steric properties of the NHC ligand are crucial to the tuning of Au I ⋅⋅⋅Au I distances. An anti‐counterfeiting application using these two salts is demonstrated. Abstract : Ex‐De CPL : Durch Modulation der Stärke der Au I ⋅⋅⋅Au I ‐ und Coulomb‐Wechselwirkungen durch Einstellung der sterischen Hinderung des Liganden zusammen mit der Materialverarbeitung zeigen die beiden chiralen Enantiomere der [Au(NHC)2 ][Au(CN)2 ]‐Doppelsalze als PMMA‐Film oder als gemahlenes Pulver eine spiegelbildliche anregungswellenlängenabhängige Photolumineszenz (Ex‐De CPL).